In vitro bioactivity and chemical investigation of Ervatamia coronaria and Tinospora crispa for the treatment of sinusitis / Heida Nadia binti Zulkefli - Zulkefli, Heida Nadia (2013)
Sinusitis can be defined as an acute or chronic inflammation of the sinuses. One of the most potent inflammatory mediators are free radicals that can be neutralized by antioxidants. The present study was carried out to evaluate in vitro antioxidant activities of Ervatamia coronaria and Tinospora crispa of petroleum ether, chloroform, methanol and water extracts using four different assays namely DPPH Radical Scavenging Assay, Metal Chelating Assay, Reducing Power Assay and Haemolysate Catalytic Assay. Total Phenolic Content Assay revealed that chloroform and methanol extracts exhibited higher phenolic content compared to petroleum ether and water extracts. It agrees with the preliminary screening on Ervatamia coronaria which exhibited pronounced antioxidant activities especially in chloroform and methanol extracts except for Metal Chelating Assay for Ervatamia coronaria (roots) which revealed that water extract exhibited pronounced antioxidant activity. Meanwhile, methanol extract of Tinospora crispa exhibited pronounced antioxidant activities in all four assays. Significant positive correlation was observed in DPPH Assay (r=0.788, p<0.01) and Reducing Power Assay (r=0.556, p<0.05) while weak correlation or no significant difference between Total Phenolic Content and Metal Chelating and Haemolysate Catalytic Assays. The extracts were further evaluated for antimicrobial activity using Disc Diffusion Assay followed by Minimal Inhibitory Concentration (MIC) and Minimal Bactericidal Concentration (MBC) against ten common sinusitis-causing microorganism namely Streptococcus pneumoniae (ATCC49619), Haemophilus influenza (ATCC49247), Moraxella catarrhalis (ATCC23296) Staphylococcus aureus, Streptococcus faecalis, Escherichia coli, Pseudomonas aeruginosa, Klebsiella pneumoniae, Proteus mirabilis and Candida albicans. Most of the extracts iii inhibited at least one of the microorganisms except for Tinospora crispa water extract which did not inhibit any of the microorganism tested. The lowest Minimal Inhibitory Concentration (3.12 mg/ml) was observed on chloroform extract of Ervatamia coronaria (stems) against Moraxella catarrhalis, methanol extract of Tinospora crispa against Streptococcus pneumoniae and petroleum ether extract of Tinospora crispa against Staphylococcus aureus. However when evaluated using the Minimal Bactericidal Concentration (MBC) Assay, only certain extracts exhibited killing against the microorganisms. Thin Layer Chromatography (TLC) was carried out to screen the chemical composition of the plant. Among the compounds identified were alkaloid, terpenoid, phenol, saponin, flavonoid and conjugated bond compound. Liquid Chromatography Mass Spectrometry (LCMS) was also carried out to identify and determine the compound in both plants. Initial investigation using LCMS/MS analysis of all sample extracts revealed the presence of large amount of alkaloids which correlated with the result from Thin Layer Chromatography (TLC). Findings of this study indeed justified the potentials of Ervatamia coronaria and Tinospora crispa as source of antioxidant agents by preventing free radicals from causing damage and subsequent inflammation to healthy tissue such as the sinus and also as source of antimicrobial agents against bacteria that cause sinusitis.